Encounter with the Plumed Serpent Drama and Power in the Heart of Mesoamerica - Aurora Pérez Jimenez, Gabina (Mesoamerican Worlds, 2007)
The Mixtec, or the people of Savi ("Nation of the Rain God"), one of the major civilizations of ancient Mesoamerica, made their home in the highlands of Oaxaca, where they resisted both Aztec military expansion and the Spanish conquest. This book presents and interprets the sacred histories narrated in the Mixtec codices, the largest surviving collection of pre-Columbian manuscripts in existence. In these screenfold books, ancient painter-historians chronicled the politics of the Mixtec from approximately a.d. 900 to 1521, portraying the royal families, rituals, wars, alliances, and ideology of the times. By analyzing and cross-referencing the codices, which have been fragmented and dispersed in far-flung archives, the authors attempt to reconstruct Mixtec history. Adding useful interpretation and commentary, Jansen and Perez Jimenez synthesize the large body of surviving documents into the first unified narrative of Mixtec sacred history.